Prediction of free fatty acid in crude palm oil using near infrared spectroscopy - Siti Nurhidayah Naqiah Abdull Rani, 1988-; Helina Abdul Rahim; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2015